Raman Multi-Omic Snapshot and Statistical Validation of Structural Differences between Herpes Simplex Type I and Epstein–Barr Viruses - Pezzotti, Giuseppe; Ohgitani, Eriko; Imamura, Hayata; Ikegami, Saki; Shin-Ya, Masaharu; Adachi, Tetsuya; Adachi, Keiji; Yamamoto, Toshiro; Kanamura, Narisato; Marin, Elia; Zhu, Wenliang; Higasa, Koichiro; et al. (International journal of molecular sciences, 2023)
Raman spectroscopy was applied to study the structural differences between herpes simplex virus Type I (HSV-1) and Epstein–Barr virus (EBV). Raman spectra were first collected with statistical validity on clusters of the respective virions and analyzed according to principal component analysis (PCA). Then, average spectra were computed and a machine-learning approach applied to deconvolute them into sub-band components in order to perform comparative analyses. The Raman results revealed marked structural differences between the two viral strains, which could mainly be traced back to the massive presence of carbohydrates in the glycoproteins of EBV virions. Clear differences could also be recorded for selected tyrosine and tryptophan Raman bands sensitive to pH at the virion/environment interface. According to the observed spectral differences, Raman signatures of known biomolecules were interpreted to link structural differences with the viral functions of the two strains. The present study confirms the unique ability of Raman spectroscopy for answering structural questions at the molecular level in virology and, despite the structural complexity of viral structures, its capacity to readily and reliably differentiate between different virus types and strains.